Knowledge description of adolescent ages 14-18 years about side effects of using fixed orthodontics - Suhartono, Budi; Novianty, Shella Indri; Zikrillah, Jassica Naufal (Odonto : Dental Journal, 2022)
Background: The use of fixed orthodontics is not a new thing for the community. The rapidly increasing information has changed people's understanding of the use of fixed orthodontic appliances where the initial function of fixed is for health, but along with changes in one's knowledge, the use of fixed orthodontics has turned into a style or trend that aims to make the appearance more attractive. Most of the youth are currently doing fixed orthodontic treatment only for a lifestyle, trend or style without knowing the complaints and goals of fixed orthodontic treatment. In addition, most teenagers do not know the orthodontic treatment that should be carried out by orthodontic specialist dentists. This study aims to specifythe description of adolescents aged 14-18 years in SMA Negeri 1 Belitang, South Sumatra province regarding the side effects of using orthodontic appliances.Method: This is a descriptive observational using a cross sectional study. The sampling technique used is total sampling with a total of 50 respondents.Result: The results of the study revealed that adolescents' knowledge of the side effects of using fixed orthodontic appliances was in the good category of 13 subjects (26%), sufficient category 29 subjects (58%), and less category 8 subjects (16%).Conclusion: The conclusion of this study is that the knowledge possessed by adolescents aged 14-18 years at SMA Negeri 1 Belitang, South Sumatra Province regarding the side effects of using orthodontic appliances is quite good in as many as 29 subjects(58%).